WOMEN ALLOCATION WORKING TIME ON PRODUCTIVE ACTIVITIES OF TRADITIONAL FISHERMEN HOUSEHOLD IN THE VILLAGE OF LERO TATARI SUB DISTRICT SINDUE DISTRICT DONGGALA - Mawar Mawar; Nurapiah Nurapiah (AGROLAND: The Agricultural Sciences Journal, 2015)
House wife fisherman in the village of Lero Tatari take an active role in the search for additional income through processing of smoked tiny fish (Rono tapa) as well as its own production of fish seller, so it does not only depend on what is done and the husband obtained. The research objective was to determine the allocation (outpouring) working time wife towards productive activities in the household in the traditional fishing in village of Lero Sub District Sindue District of Donggala, respondents were used as the object of research is the woman selling fish in traditional fishing households. The analytical method used the descriptive method of qualitative and quantitative analysis of the activities and magnitude of the outpouring of women working in the processing and marketing of fish products produced on productive activities in traditional fishing households. The results showed that the household head fisherman in the village of Lero Tatari work as traditional fishermen operate fishing gear lift nets, while housewives work as traders fish and processed fish (smoked fish). Stages of productive activities that take place every day in the household is the catch of fishermen in the village of Lero sold to his wife or wives of the fishermen who will process the catch into smoked fish (smoked tiny fish) with local language Rono tapa. Fish that have been processed then sold by the wife or wives of the fishermen to the market in the provincial capital (Palu). The number of outpouring work by woman selling fish is that HOK.   Key Words : Allocation Working Time, traditional fishermen, Women Fish seller.